Crossing the linguistic causeway: a binational approach for translating soundscape attributes to Bahasa Melayu - Lam, Bhan; Chieng, Julia; Watcharasupat, Karn N.; Ooi, Kenneth; Zhen, Ting Ong; Joo, Young Hong; Woon, Seng Gan (Elsevier, 2022)
Translation of perceptual descriptors such as the perceived affective quality attributes in the soundscape standard (ISO/TS 12913–2:2018) is an inherently intricate task, especially if the target language is used in multiple countries. Despite geographical proximity and a shared language of Bahasa Melayu (Standard Malay), differences in culture and language education policies between Singapore and Malaysia could invoke peculiarities in the affective appraisal of sounds. To generate provisional translations of the eight perceived affective attributes — eventful, vibrant, pleasant, calm, uneventful, monotonous, annoying, and chaotic — into Bahasa Melayu that is applicable in both Singapore and Malaysia, a binational expert-led approach supplemented by a quantitative evaluation framework was adopted. A set of preliminary translation candidates were developed via a four-stage process, firstly by a qualified translator, which was then vetted by linguistics experts, followed by examination via an experiential evaluation, and finally reviewed by the core research team. A total of 66 participants were then recruited cross-nationally to quantitatively evaluate the preliminary translation candidates. Of the eight attributes, cross-national differences were observed only in the translation of annoying. For instance, menjengkelkan was found to be significantly less understood in Singapore than in Malaysia, as well as less understandable than membingitkan within Singapore. Results of the quantitative evaluation also revealed the imperfect nature of foreign language translations for perceptual descriptors, which suggests a possibility for exploring corrective measures.